2015
DOI: 10.1002/14651858.cd001287.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Mucolytic agents versus placebo for chronic bronchitis or chronic obstructive pulmonary disease

Abstract: Mucolytic agents versus placebo for chronic bronchitis or chronic obstructive pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 41 publications
1
20
0
4
Order By: Relevance
“…Mucolytics A Cochrane review of 34 studies showed that a mucolytic therapy in patients with COPD increases the likelihood of being exacerbation free [67], compared with placebo. The number needed to treat (to keep an additional patient free from exacerbations for an average of 10 months) was eight.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…Mucolytics A Cochrane review of 34 studies showed that a mucolytic therapy in patients with COPD increases the likelihood of being exacerbation free [67], compared with placebo. The number needed to treat (to keep an additional patient free from exacerbations for an average of 10 months) was eight.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…170,171 Due to the heterogeneity of studied populations, treatment dosing and concomitant treatments, currently available data do not allow one to identify precisely the potential target population for antioxidant agents in COPD.…”
Section: Mucolytic (Mucokinetics Mucoregulators) and Antioxidant Agementioning
confidence: 99%
“…Было сделано заключение, что долгосрочная терапия на протяжении 6 месяцев хрониче-ского бронхита Миртолом стандартизированным снижает частоту и интенсивность рецидивов [15]. Данное клиниче-ское исследование учитывалось в Кохрановском цен-тральном регистре контролируемых исследований среди отобранных 34 из нескольких сотен работ и одно из немногих получило 4 из 5 возможных баллов при оценке качества [16].…”
Section: хронический бронхитunclassified